2020
DOI: 10.1007/978-3-030-43823-4_18
|View full text |Cite
|
Sign up to set email alerts
|

Sampling, Intervention, Prediction, Aggregation: A Generalized Framework for Model-Agnostic Interpretations

Abstract: Model-agnostic interpretation techniques allow us to explain the behavior of any predictive model. Due to different notations and terminology, it is difficult to see how they are related. A unified view on these methods has been missing. We present the generalized SIPA (sampling, intervention, prediction, aggregation) framework of work stages for model-agnostic interpretations and demonstrate how several prominent methods for feature effects can be embedded into the proposed framework. Furthermore, we extend t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
(39 reference statements)
1
25
0
1
Order By: Relevance
“…If this number is exceeded, production of waste tends to be higher. These findings are consistent with some studies that have reported a directly proportional relationship between the size of buildings and the generation of waste [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…If this number is exceeded, production of waste tends to be higher. These findings are consistent with some studies that have reported a directly proportional relationship between the size of buildings and the generation of waste [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 93%
“…Other studies developed a general regression neural network (GRNN) model for the prediction of annual municipal solid waste (MSW) generation at the national level for 44 countries of different size, population and economic development level [ 9 ]. Deep learning model combined with permutation-based VI scores method (R package “vip”) [ 44 ] and individual conditional expectation (ICE) plots method [ 45 ] was the very innovative and modern approach of the study of this paper to forecast MSW independent variables, to determine the factors that most influence the variables and to estimate how much they affect them. In addition, MSW production, separate collection, and MSW management costs with the same database were considered in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our first model-agnostic method is based on a simple feature importance ranking measure (FIRM); for details, see Greenwell et al (2018), Zien et al (2009), and Scholbeck et al (2019). The specific approach used here is based on quantifying the "flatness" of the effects of each feature.…”
Section: Variance-based Methodsmentioning
confidence: 99%
“…To evaluate the order of importance of the variables and related graphic processing, the permutation-based VI scores method [36] was used. For this method, in particular, the package "vip" version 0.1.3.9000 of the program R (Brandon Greenwell, Cincinnati, Ohio) was used [37].…”
Section: Statistical Analysesmentioning
confidence: 99%